SURVEY POTENSI SUNGAI WARIORI ( SP 9 ) DISTRIK MASNI SEBAGAI PEMBANGKIT TENAGA LISTRIK SKALA KECIL ( PLTMh ) DIKABUPATEN MANOKWARI PROPINSI PAPUA BARAT: POTENTIAL SURVEY OF THE WARIORI RIVER ( SP 9 ) MASNI DISTRICT AS A SMALL SCALE ELECTRICITY POWER PLANT (PLTMh) IN MANOKWARI REGENCY, WEST PAPUA PROVINCE - Bibiana Rosalina Wihyawari (Universitas Papua, 2014)
This study is dealing with Warioryriver masni Development calculation of the water flow and power potential of water as a Power Plant Micro Hydropower ( MHPP ).Potention survey wariory river calculating water flow, power potential an four sample.Calulating water flow and power potention as reached wariory river as 152 kW . Calculating water survey river wariory water flow and power potention. Output calculating river warioryis very power potential fora Power Plant Micro Hydropower ( MHPP ).